Is there a common genetic basis for autoimmune diseases? (2006)
ABSTRACT: Autoimmune diseases (ADs) represent a diverse collection of diseases in terms of their demographic profile and primary clinical manifestations. The commonality between them however, is the damage to tissues and organs that arises from the response to self-antigens. The presence of shared pathophysiological mechanisms within ADs has stimulated searches for common genetic roots to these diseases. Two approaches have been undertaken to sustain the "common genetic origin" theory of ADs. Firstly, a clinical genetic analysis showed that autoimmunity aggregates within families of probands diagnosed with primary Sjögren's (pSS) syndrome or type 1 diabetes mellitus (T1D). A literature review supported the establishment of a familiar cluster of ADs depending upon the proband's disease phenotype. Secondly, in a same and well-defined population, a large genetic association study indicated that a number of polymorphic genes (i.e. HLA-DRB1, TNF and PTPN22) influence the susceptibility for acquiring different ADs. Likewise, association and linkage studies in different populations have revealed that several susceptibility loci overlap in ADs, and clinical studies have shown that frequent clustering of several ADs occurs. Thus, the genetic factors for ADs consist of two types: those which are common to many ADs (acting in epistatic pleitropy) and those that are specific to a given disorder. Their identification and functional characterization will allow us to predict their effect as well as to indicate potential new therapeutic interventions. Both autoimmunity family history and the co-occurrence of ADs in affected probands should be considered when performing genetic association and linkage studies.